Absence of Activation-induced Cytidine Deaminase, a Regulator of Class Switch Recombination and Hypermutation in B Cells, Suppresses Aorta Allograft Vasculopathy in Mice. Issue 8 (August 2015) - Nakanishi, Tomonori; Xu, Xiaoyan; Wynn, Carmen; Yamada, Toshiko; Pan, Fan; Erickson, Laurie; Teo, Haeman; Nakagawa, Terry; Masunaga, Taro; Abe, Jumpei; Akamatsu, Masahiko; Tamura, Kouichi; et al.
Abstract : Background: Antibody-mediated rejection is caused in part by increasing circulation/production of donor-specific antibody (DSA). Activation-induced cytidine deaminase (AID) is a key regulator of class switch recombination and somatic hypermutation of immunoglobulin in B cells, yet its role in antibody-mediated transplant rejection remains unclear. We show here that AID deficiency in mice enables suppression of allograft vasculopathy (AV) after aorta transplantation, a DSA-mediated process. Methods: Splenocytes from C57BL/6 J (B6) AID −/− mice were used for determining in vitro proliferation responses, alloreactivity, cell surface marker expression, and antibody production. BALB/c mouse aortas were transplanted into B6 AID −/− mice with or without FK506 treatment. Blood and aorta grafts were harvested on day 30 after transplantation and were subjected to DSA, histological, and immunohistological analyses. Results: The AID −/− splenocytes were comparable to wild type splenocytes in proliferation responses, alloreactivity, and expression of cell surface markers in vitro. However, they completely failed to produce immunoglobulin G, although they were not impaired in immunoglobulin M production relative to controls. Furthermore, BALB/c aorta grafts from B6 AID −/− recipient mice on day 30 after transplantation showed reduced signs of AV compared to the grafts from B6 wild type recipient mice which had severe vascular intimal hyperplasia, interstitial fibrosis, and inflammation. Treatment with FK506 produced a synergistic effect in the grafts from AID −/− recipients with further reduction of intimal hyperplasia and fibrosis scores. Conclusions: The AID deficiency inhibits DSA-mediated AV after aorta transplantation in mice. We propose that AID could be a novel molecular target for controlling antibody-mediated rejection in organ transplantation. Abstract : Activation-induced cytidine deaminase is a key regulator of class switch and is demonstrated in this study to be relevant to the development of antibody-mediated rejection in a mouse model.